IMPLEMENTASI PENDIDIKAN BUDAYA DAN KARAKTER BANGSA DALAM BUDAYA SEKOLAH - Susanto, Rochmad Dwi; Zuriah, Nurul; Syahri, Mohamad (Jurnal Civic Hukum, 2017)
Education and culture to be very fundamental national character is created and maintained for the values of good character , namely : value , religious , honest , tolerance , discipline , hard work , creative, independent , democratic , curiosity , the spirit of nationalism , patriotism , appreciate the achievements , friends / communicative , love peace , love reading , environmental care , social care and responsibility . This research was conducted at SMP Negeri 3 Malang , with the aim of : ( 1 ) To describe the implementation of National Character Education Culture And Culture In Schools " Bintaraloka " ( Adi Taruna Loka Bina ) in i SMP Negeri 3 Malang . ( 2 ) To describe the factors supporting and inhibiting factors in the implementation of Culture and National Character Education In School Culture " Bintaraloka " ( Adi Taruna Loka Bina ) in SMP Negeri 3 Malang . ( 3 ) To describe an attempt to address the factors inhibiting the implementation of Culture and National Character Education In School Culture " Bintaraloka " ( Adi Taruna Loka Bina ) in SMP Negeri 3 Malang.This study uses qualitative research techniques. Where researchers directly involed in collecting information related to the title of the study. The collection of data obtained by observation, interviews, and documentation. The informant who need be exstractedinformation is principal of SMP Negeri 3 Malang, Student Waka, Waka Infrastructur, Teachers and Student Civics classes VII, VIII and IX. Then the data were analyzed by descriptive qualitative.The results showed that the implementation of the nation's culture and character education in the school culture " bintaraloka " in SMP Negeri 3 Malang applied through routine school activities , school programs , Through programs such as the school Friday clean , . Through self-development such extracurricular scouts, music, sports , honesty canteen facilities and student council . In addition, through subjects to teachers always give a good role models... The solution is a school needs to provide outreach to all piha from parents, and establish relationships with others in the development of education pihal culture and national character itself.